Voicing the Web: The Trajectories of Blogging in the United States and France - Siles González, Ignacio (2014)
The World Wide Web has turned into an important means to share voice, that is, the narratives through which individuals give a public account of their lives. This dissertation analyzes how this key cultural process came into being and discusses some of its main implications. To this end, it studies one specific technology of subjectivity that embodies this process in fundamental ways: the blog. This dissertation examines the processes that have shaped practices of subjectivity on the Web in two countries (the United States and France) from the mid-1990s to the early years of the 2010s. The focus is on three processes: the emergence of the blog; its constitution into a means for intervening in the public sphere and a commodity; and the identity crises triggered by the rise of novel media technologies (such as “microblogging”) designed to replace or extend it. A theoretical framework is developed that makes four analytic contributions: (a) it considers media technologies as assemblages of both textual meaning and material artifacts; (b) it analyzes both the production and use of media technologies; (c) it adopts a process-orientation to make sense of the temporal development of the Web; and (d) it implements a comparative approach to identify the similarities and differences between the cases under study. Drawing on interviews with key actors, content and artifact analyses of websites, traditional archival research, and online archival research, this dissertation examines how users and software developers have enacted particular notions of the self, conceived the publicness of their Web appropriation and development practices, and built and utilized media technologies such as websites and software programs to these ends. The analysis reveals that the cultural identity of blogging as a practice of subjectivity in these two countries is neither inevitable nor neutral. In the United States, particular liberal notions and neoliberal assumptions have informed the imaginary surrounding blogs in crucial ways. The study also shows how and why actors in France have gradually abandoned traditional makers of exceptionalism that were key in the development of the country’s national identity and favored notions that characterize the United States instead.